Management and organization theory a Jossey-Bass reader - Miles, Jeffrey Allen, 1963- (Jossey-Bass business & management series., 2012)
"A "must-have" for any MBA/PhD in management and organizations, this reader is the first to name, describe, and explore each of the top 50 most popular, most researched, and most used management and organization theories to date. Organized to correspond to leading management textbooks, this Jossey-Bass Reader provides detailed information about each theory, including major survey instruments used to measure variables in the theory; major questions examined; significant figures who have published on the theory, strengths and weaknesses of the theory; practical applications; and seminal articles published for the theory"--